How judges dissent: A comparative rhetorical and metadiscursive analysis of European Court of Human Rights (ECtHR) and U.S. Supreme Court separate opinions - Notari, Fabiola (Comparative Legilinguistics, 2025)
Dissenting opinions reveal how personal values and professional courtesy shape judicial discourse, reflecting a delicate rhetorical balance between individual judgment and institutional collegiality (Garzone, 2016; Etxabe, 2022). This balance takes on particular significance as English increasingly functions as a judicial lingua franca, notably in human rights adjudication. Yet, comparative studies investigating how judges from diverse legal traditions rhetorically calibrate their “positioning” (individual stance) and “proximity” (heteroglossic engagement with majority and dissenting voices) remain scarce (Hyland, 2015). To address this gap, the present study adopts a mixed-methods approach, combining rhetorical move analysis (Swales, 1990; Bhatia, 1993) with Hyland’s interpersonal metadiscourse framework (2005, 2010). Specifically, it analyzes 112 dissenting opinions from two influential courts: the European Court of Human Rights (ECtHR), which addresses an international readership, and the U.S. Supreme Court, whose audience is primarily domestic yet influential at a global level. Findings reveal a shared rhetorical blueprint composed of nine core moves, newly identified in this study, which extend Goźdź-Roszkowski’s (2020) taxonomy. These moves, however, are instantiated differently in the two institutional contexts analysed. U.S. dissents emphasize logical signposting and authoritative citation of precedents, whereas Strasbourg dissents foreground sustained doctrinal elaboration and explicit judicial self-reference. These variations illustrate how judges strategically craft their moves to reconcile institutional norms with individual stance-taking and audience expectations, deepening our understanding of judicial dissent as a distinctive genre and pointing to promising avenues for further research.